Kebijakan Hukum Pidana Dalam Menanggulangi Tindak Pidana Pencucian Uang Melalui Gatekepeer - Cindy Amelia; Zaid Alfauza Marpaung (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Criminal law policy is a science as well as an art that ultimately has the practical purpose of enabling positive legal regulations to be better formulated and to provide guidance not only to law makers and also to organizers or implementers of court decisions. Perpetrators of money laundering usually use the services of professional professionals (gatekeepers), which include the profession of Advocates, notaries, PPAT, and others. The profession is also required to take responsibility in preventing and combating money laundering. The research method used in this study is a normative juridical approach, in order to eradicate money laundering, the Government of Indonesia and the House of Representatives have established a number of legal products, one of which is Law No. 15 of 2002 which has been amended by Law No. 25 of 2003 on money laundering and last amended by Law No. 8 of 2010 on the Prevention and Eradication of money laundering. Keywords: policy, anti Money Laundering, Gatekeeper [1] Korespondensi : cindyamelia9863@gmail.com [2] Dosen Universitas Islam Negeri Sumatera Utara